Peningkatan Pendapatan Ibu-Ibu Rumah Tangga Melalui Pelatihan Pembuatan Kompos Ela Sagu dan Aplikasinya pada Tanaman Sayuran di Desa Tawari Kotamadya Ambon - Elizabeth Kaya; L Joris; J A Putinella (Universitas Perjuangan Tasikmalaya, 2026)
Sago Palm in often utilized for its starch, mean while the inside fibre material of sago palm is a waste as left-over. Cattle dung as an activator in composting is usually found easily, because there are many cattles as livestocks. Because the sago palm waste and cattle dung are not effectively used, there are problems such as bad odor and environmental pollution. This science and technology application aimed to improve the knowledge and skill of cattlestock housewive farmers who are involued in a PKK group in Tawiri village on the palm sago waste composting as a fertilizer for vegetable production and to increase family income. The method used were extension, training and application of the compost on the farmer’s field by planting water spinach. The result of the extension of composting showed that the minimum knowledge of participants increased after following the lecture, meanwhile the final evaluation showed that the participants are able to make compost from sago palm waste and have seen the benefit of sago palm compost on the soil fertility and water spinach production.